Functional Genomics of Wood Quality and Properties - Tang, Wei; Luo, Xiaoyan; Nelson, Aaron; Collver, Hilary; Kinken, Katherine (My University, 2003)
Genomics promises to enrich the investigations of biology and biochemistry. Current advancements in genomics have major implications for genetic improvement in animals, plants, and microorganisms, and for our understanding of cell growth, development, differentiation, and communication. Significant progress has been made in the understanding of plant genomics in recent years, and the area continues to progress rapidly. Functional genomics offers enormous potential to tree improvement and the understanding of gene expression in this area of science worldwide. In this review we focus on functional genomics of wood quality and properties in trees, mainly based on progresses made in genomics study of Pinus and Populus. The aims of this review are to summarize the current status of functional genomics including: (1) Gene discovery; (2) EST and genomic sequencing; (3) From EST to functional genomics; (4) Approaches to functional analysis; (5) Engineering lignin biosynthesis; (6) Modification of cell wall biogenesis; and (7) Molecular modelling. Functional genomics has been greatly invested worldwide and will be important in identifying candidate genes whose function is critical to all aspects of plant growth, development, differentiation, and defense. Forest biotechnology industry will significantly benefit from the advent of functional genomics of wood quality and properties.
Keywords: gene discovery, genomic sequencing, lignin biosynthesis, cell wall biogenesis, expression profiling